2001
DOI: 10.1177/154596830101500109
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelations Between Disability and Quality of Life in Patients with Multiple Sclerosis in the Area of Bajo Aragon, Spain: A Geographically Based Survey

Abstract: Multiple sclerosis (MS) is one of the most disabling diseases in young people, but the interrelation between disability and quality of life is poorly understood. As individual correlations between disability and the perspective of the patient may be weak in individual subjects, the purpose of our work was to analyze and correlate quality of life with neurologic impairment and disability in all patients with MS from the geographic area of the Bajo Aragón in the northeastern region of Spain. A total of 36 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
6
22
0
1
Order By: Relevance
“…This was previously also confirmed in other countries [13][14][15][16]. It has been shown that even in the early stage of disease, patients' QoL is significantly reduced [17].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This was previously also confirmed in other countries [13][14][15][16]. It has been shown that even in the early stage of disease, patients' QoL is significantly reduced [17].…”
Section: Discussionsupporting
confidence: 80%
“…Chronic and progressive diseases like MS seem to particularly modify an individual's QoL. This is confirmed by studies conducted in Sweden, Germany, Spain, the United States and Canada [13][14][15][16][17]. However, because of cultural and social differences and the organization of the health care system, the results of these studies cannot be directly linked to MS patients in Poland [18].…”
Section: Introductionsupporting
confidence: 61%
“…71 The original version of the FAMS is a very useful disease-targeted instrument to evaluate MS patients' HRQoL. 15,67,68 However, we feel that the modified FAMS offers a more holistic assessment of neurological symptoms and psychosocial complaints associated with MS in line with published recommendations regarding specific HRQoL instruments. 57,71 Hamburg Quality of Life Questionnaire in Multiple Sclerosis…”
Section: Functional Assessment Of Multiple Sclerosismentioning
confidence: 78%
“…In their comparison of multiple QOL measures, Nicholl et al found that the FAMS was the most sensitive measure of the functional domains often associated with decreased QOL in MS patients [88]. In a study that assessed QOL among patients with MS in Spain, MS disability was related to emotional well-being (depression), mobility, and physical symptoms [89]. This study confirms that although depression is certainly a factor in adjustment to MS-related disability, other issues must also be considered and assessed.…”
Section: Assessment Of Depressionmentioning
confidence: 99%